Increasing the service level index through implementing lean warehousing tools in a trading household equipment company - Pachauri Carbajal, Ana Karin (2024)
The commercial sector represents a fundamental part of Peru's economy and has been growing exponentially in recent years. However, like any other sector, it is affected by various challenges that affect customer satisfaction, the impact of which has a direct effect on sales. Therefore, in this case study, a set of tools such as the 5S methodology, Kaizen and standardized work were defined, which will focus on the optimization of this indicator and the solution of its root causes. Likewise, the improvements were validated through a pilot test and the use of Arena software. The results obtained were positive, since there was a time reduction in the search for tools from 8 minutes to 4 minutes, and the cycle time decreased from 15 minutes to 10 minutes. The material shortage rate improved from 29% to 10% and finally the efficiency was maximized from 48.41% to 64%. All these results generated an increase from 87% to 94% in the main indicator, which is the level of service. This research proposes a new model combining Lean Warehousing, Kaizen, 5s and Standard work applied in a kitchen commercialization company, which would help other companies in the same sector to optimize the picking and packing processes and increase the level of service. It should be noted that there are not many case studies using these methodologies, so the aim is to disseminate and validate these methodologies in a new scenario.